2018
DOI: 10.1186/s12935-018-0691-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of methylation-driven genes for monitoring and prognosis of patients with lung adenocarcinoma

Abstract: BackgroundAs one of the most common malignant tumors in humans, lung cancer has experienced a gradual increase in morbidity and mortality. This study examined prognosis-related methylation-driven genes specific to lung adenocarcinoma (LUAD) to provide a basis for prognosis prediction and personalized targeted therapy for LUAD patients.MethodsThe methylation and survival time data from LUAD patients in the TCGA database were downloaded. The MethylMix algorithm was used to identify the differential methylation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…Zhao et al developed a TCGA‐based model using 20 filtered genes that showed lower accuracy (61.5% vs. 67%) for predicting OS compared to ours . Gao et al established a TCGA‐based survival model using methylation‐driven genes that was also inferior to ours (66% vs. 67%) …”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Zhao et al developed a TCGA‐based model using 20 filtered genes that showed lower accuracy (61.5% vs. 67%) for predicting OS compared to ours . Gao et al established a TCGA‐based survival model using methylation‐driven genes that was also inferior to ours (66% vs. 67%) …”
Section: Discussionmentioning
confidence: 71%
“…43 Gao et al established a TCGA-based survival model using methylation-driven genes that was also inferior to ours (66% vs. 67%). 44 There were several limitations to our study. First, the investigated cohort was retrieved from TCGA and no external validation cohort was available.…”
Section: Discussionmentioning
confidence: 93%
“…Another study conducted integrated analysis on TCGA data to get a better understanding of molecular mechanisms involved in esophageal squamous cell carcinoma, contributing to a more precise prognosis detection [23]. What is more, a study concentrated on lung adenocarcinoma found out several hub genes that could be employed to facilitate early diagnosis and accurate prognosis assessments of patients [24]. In the present study, methylation microarray dataset (GSE87053) and gene expression microarray dataset (GSE23558) were analyzed through R language and a total of 255 hypermethylated-down-regulated genes and 114 hypomethylated-upregulated genes were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we used the MethylMix R package with the screening criteria (|logFC|>0, P<0.05, Cor<-0.3) to extract the methylation-driven genes. Analysis of average methylation differences at 3000 bp (base pair) sites upstream of genes to identify differential methylation levels in gene promoters [23][24][25]. The differential level of methylation in the promoter of genes was performed by using the limma R package [26].…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…Currently, few studies based on using MethylMix R package to identify specific methylation-driven genes have been reported [20][21][22]. Recently, a study based on MethylMix reveals potential prognostic methylationdriven genes for predicting the prognosis in lung adenocarcinoma (LUAD) has been reported [23]. In the present study, we extracted the DNA methylation and RNA-Seq data using bioinformatics methods from The Cancer Genome Atlas (TCGA) database, and then the MethylMix R package was performed to obtain methylation-driven genes.…”
Section: Introductionmentioning
confidence: 99%